Biomassa e nutrientes na serrapilheira em complexo rupestre de granito, Mimoso do Sul, ES - Freitas, Carlos Antônio Araújo de (2013)
Forest ecosystems found in areas with rocky outcrop require more detailed studies on the processes of nutrient cycling. Within these processes, vegetation ecosystems returns nutrients to the soil through the circulation of matter, which is represented by the litter (waste vegetable leaves, branches, stems, barks, fruits and flowers). This study aimed to quantify the accumulation and deposition of biomass levels and content of nutrients in the litter, as well as correlating with climatic variables (rainfall and temperature) analyzing the temporal variation of nutrients on Complex Rupestre Granite, located in the municipality Mimoso do Sul, Epírito Santo state. Sampling of litter accumulated was conducted in five transects of 50m x 2m. In each transect, 10 samples were collected with the aid of a template 0,25 m x 0,25 m (0.0625 m2), totaling 50 samples per month. After collection, the samples were brought to the laboratory and separated in the fraction called 'Other species', with the presence of leaves, twigs, flowers, fruits and material not identifiable from several species; fraction 'Pseudobombax' material identifiable species Pseudobombax aff. campestre, which were subsequently dried and weighed. The accumulated biomass for fractions was converted to kg ha-1, that by this extrapolation was calculated also the contents of macro and micronutrients. The study period was accumulated litter from May 2011 to April 2012. The deposited litter was sampled in the same transects, which were distributed in each of three collectors positioned below the canopy of P. aff. campestre, with 0.5 mx 0.5 m and 0.70 m above ground level, with nylon mesh screens of 2 mm, a total of 15 collectors. Was collected monthly, and adopted the same procedures litter accumulated. The sample period of the litter was placed from November 2011 to October 2012. For the evaluation of the monthly variation of the biomass of each fraction, it was considered a completely randomized design (CRD), where treatments for the months of the year (12 treatments) and repetitions transects (5 repetitions). To determine the monthly variation of the concentration of each fraction was used the same CRD with the same treatment (12 months of the year) and repetitions were represented by three replicates (3 replicates) taken from a homogenized sample milled type Wiley. For the analysis of correlation with climatic variables in both fractions, we used the PEARSON correlation. The results were tested with a 5% level of probability. Litter accumulated average was 8900 kg ha-1 and deposited 5400 kg ha-1. There were peaks of accumulation and deposition at the end of the dry season, thus demonstrating a seasonal. Litter accumulated in both the levels and the content, the highest concentrations of macronutrients were N and Ca, Fe and micronutrient was The only nutrient that had a significant correlation with climatic variables were: N, P and S for both fractions and variables, Fe and Cu in fraction Pseudobombax for both variables. The total accumulation of macronutrients was 292.42 kg ha-1 and micronutrients was 10.34 kg ha-1. Litter deposited, both the contents and the content, the highest deposition of macronutrients N and Ca, and boron was Mn. The only nutrient that had a significant correlation with climatic variables were: N for both fractions in variable rainfall, P, Mg, Mn and B, for the fraction of other species in the variable temperature, and Cu in fraction Pseudobombax in variable temperature. The total deposition of macronutrients was 203.23 kg ha-1 and micronutrients were 3.62 kg ha-1. The efficient use of nutrients, S and Cu were the macro and micronutrient respectively greater efficiency by species of the site, as well as the P. aff. campestre was efficient for all nutrients.